THUCYDIDES AND LAW: A RESPONSE TO LEITER. (18th December 2013) - Shanske, Darien
Abstract : Thucydides is the author of the most harrowing account of societal breakdown in antiquity. Brian Leiter has recently made the provocative claim that Thucydides' analysis of such breakdowns indicates that morality is of little import in guiding behavior, including legal behavior. Yet Thucydides also narrates events, particularly in Athens, that indicate that something resembling morality can continue to guide action, including legal action, even at the worst of times. Thucydides provides tantalizing clues as to why he narrates events that only sometimes follow the path predicted by Leiter. In particular, Thucydides (accurately) portrays the law that suffuses Athenian life and saves Athens itself as, for the most part, informal and infused with moral concerns. Leiter's reading of Thucydides therefore not only is limited but misses implicit arguments that challenge Leiter's broader argument for a particular form of legal realism.